(untitled) (Journal of Geography and Environmental Management, 2018)
The materials related to organization of curatively-health tourism in the Shalkar district of Aktobe area are presented in train aid. The unique natural curative resources of the investigated region are examined. In the areadistrictthere are widespread and unique natural curative resources that is actively used on the local enterprises of making healthy. For these sanatorium- resort organizations the multi-fieldness is characteristic at treatment and prophylaxis of diseases of man. The sanatorium-resort complex of the Aktobe area of region possesses competitive edges, such as a presence of unique natural curative resources, availability of sanatorium- resort services in a price criterion for persons with the different level of income, positive dynamics of load factor, implementation of principle of self-repayment, positive dynamics of indexes of business activity, presence of highly skilled shots.In the article, the special attention is spared to organization of resort place.